The efficacy of targeted vs nontargeted tactics in war termination - Jackson, Alyssa (Kansas State University, 2016)
BACKGROUND AND PURPOSE: Recent studies regarding war termination and the bargaining model of war focus on how belligerents use coercion to reach a war settlement, but neglect the importance of tactical decisions. Although strategies are the principal tool used to conduct war, only significant tactical achievements lead to significant strategic achievements. METHOD: In this paper I analyze the tactics employed in two case studies, the Second Boer War between Great Britain and the South African Boers and the Winter War between the Soviet Union and Finland. Using the bargaining model of war, I discuss two categories of tactics. Targeted tactics focus on destroying the enemy’s critical vulnerabilities and dislocating their strengths while minimizing one’s own vulnerabilities. Nontargeted tactics focus on centers of gravity, employing military strength in an effort to overwhelm enemy forces with superior resources and technology. RESULTS: I demonstrate that tactics have a marked impact on the duration and outcome of warfare and targeted tactics minimize the cost of fighting in order to achieve strategic objectives and increase the bargaining advantage. CONCLUSION: Targeted tactics are a significant tool in warfare that affect war termination and hold the potential to increase the bargaining advantage at a lesser cost.
Keywords: Political science; Security studies; Bargaining model of war; Tactics; Conflict; War termination